"It's not really a menu because we can't pick what we want to do": Content integration in kindergarten contexts. Issue 3 (September 2015) - Heimer, Lucinda Grace; Klefstad, Erica
In our research, we critique current curricular practices as enacted by teachers in kindergarten settings for five-year-olds (5K) in the United States. We explore how teachers of 5K students understand and implement early childhood integrated curriculum regulated by standards and assessments. In the United States, integrated curriculum guidelines are well known and taught throughout the pre-kindergarten community, are considered developmentally appropriate by Western notions, and are recommended for teaching children birth through age eight. Integrated curriculum is commonly modeled in early childhood classrooms; however, there is a dearth of research regarding implementation of such an approach at the elementary level (typically kindergarten through fifth grade). In fact, with a focus on accountability toward proficiency for all children in the United States (Race to the Top; Common Core Standards; Danielson Teacher Effectiveness Evaluations; edTPA), there has been an increased focus on discrete content area instruction. Our data include classroom observations and interviews with teachers in eight public and private 5K classes across a southeastern region of a US Midwestern state. We highlight the increased rigidity for "block content area" time in public school settings and the difficulty in following the interests of children and integrating curriculum across content areas. We call attention to the impact of increasingly regulated classroom time and subsequent regulation of teachers and childhood and suggest the creation of hybrid mentoring spaces to revisit the goal of early education and support teachers' enactment of policy.